2009
DOI: 10.1124/jpet.108.145888
|View full text |Cite
|
Sign up to set email alerts
|

Smoke, Choline Acetyltransferase, Muscarinic Receptors, and Fibroblast Proliferation in Chronic Obstructive Pulmonary Disease

Abstract: Acetylcholine (ACh), synthesized by choline acetyltransferase (ChAT), and muscarinic M 1 , M 2 , and M 3 receptors (MRs) are involved in fibroblast proliferation. We evaluated ChAT, MRs, and extracellular signal-regulated kinase (ERK) 1/2 and nuclear factor (NF) B activation in lung fibroblasts from patients with chronic obstructive pulmonary disease (COPD), control smokers, and controls. Human fetal lung fibroblasts (HFL-1) stimulated with interleukin (IL)-1␤, tumor necrosis factor (TNF)-␣, and cigarette smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 32 publications
(43 reference statements)
8
62
0
Order By: Relevance
“…However, in vitro studies have indicated that ACh can induce proliferation of lung fibroblasts [20], and collagen synthesis by these cells [22]. In addition, increased ChAT expression has recently been found in lung fibroblasts from healthy smokers and from COPD patients [15], suggesting that non-neuronal ACh may modulate fibroblast function in an autocrine fashion under these conditions. Our results demonstrated that tiotropium inhibits LPS-induced collagen accumulation in the lung and airway wall, indicating that ACh may be a key regulator of airway fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vitro studies have indicated that ACh can induce proliferation of lung fibroblasts [20], and collagen synthesis by these cells [22]. In addition, increased ChAT expression has recently been found in lung fibroblasts from healthy smokers and from COPD patients [15], suggesting that non-neuronal ACh may modulate fibroblast function in an autocrine fashion under these conditions. Our results demonstrated that tiotropium inhibits LPS-induced collagen accumulation in the lung and airway wall, indicating that ACh may be a key regulator of airway fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ACh-synthesising enzyme choline acetyltransferase (ChAT), as well as muscarinic receptors, are expressed in both structural and inflammatory cells in the lung [12]. Remarkably, increased ChAT expression was found in lung fibroblasts from smokers and COPD patients [15]. Muscarinic M 3 receptor stimulation has been shown to increase the release of neutrophil chemotactic activity by alveolar macrophages [16], induce interleukin (IL)-8 release by bronchial epithelial cells [17] and monocytes [18], and augment cigarette smoke-induced IL-8 release by ASM cells [19].…”
mentioning
confidence: 96%
“…Human lung fibroblasts were isolated from surgical specimens of human bronchi as previously described [20]. To confirm the purity of the cultured fibroblasts, the recovered cells were identified by their morphology, adherent nature, expression of vimentin and types I and III collagen, and lack of expression of cytokeratin, α-smooth muscle actin, factor VIII and CD45.…”
Section: Isolation and Culture Of Lung Fibroblasts From Patientsmentioning
confidence: 99%
“…Purified lung fibroblasts from COPD, HS, and C subjects were grown in a humidified atmosphere containing 5% CO 2, and passaged by trypsinization at nearly confluence onto 100 mm culture plates as previously described [20].…”
Section: Isolation and Culture Of Lung Fibroblasts From Patientsmentioning
confidence: 99%
“…Stimulation of the vagus nerve in patients with depression significantly increased levels of transforming growth factor beta (TGF-β) , a substance which promotes fibrosis [13], while vagotomy eliminated the drug-induced activation of TGF-β in cerebrospinal fluid [14]. ACh can also activate M receptors to promote fibroblast proliferation in the lung [15]. Additionally, maternal nicotine exposure increased levels of collagen mRNA in pulmonary fibroblasts via α-7nAChR [16].…”
Section: The Vagus Nervementioning
confidence: 99%